1978
DOI: 10.1002/cpt197824152
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of intravenous and intramuscular morphine

Abstract: The disposition of parenteral morphine was assessed in two pharmacokinetic studies. In Study 1, 10 mg of morphine sulfate was administered by intravenous (IV) infusion, intramuscular (IM) injection, or both, to 8 healthy young adult male volunteers. Plasma morphine concentrations were determined by radioimmunoassay in multiple blood samples drawn after each dose. Mean (+/-SE) kinetic parameters following IV morphine were: volume of distribution (Vd), 3.2 (+/- 0.3) L/kg; elimination half-life (t1/2beta), 2.9 (+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(74 citation statements)
references
References 13 publications
(22 reference statements)
9
64
1
Order By: Relevance
“…Morphine is reported to have a high extraction ratio of 0.7 after intravenous administration in healthy volunteers 37. For a drug with a high extraction ratio, in general, hepatic blood flow is the rateā€limiting factor for drug elimination through the liver, which we confirmed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Morphine is reported to have a high extraction ratio of 0.7 after intravenous administration in healthy volunteers 37. For a drug with a high extraction ratio, in general, hepatic blood flow is the rateā€limiting factor for drug elimination through the liver, which we confirmed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In combination with mild preanesthetics and muscle paralysis, almost identical anesthetic regimens (70/30% N,O and morphine in doses equal to those used in the present study) have been shown to be fully adequate for abdominal surgery in humans (Stanski et al, 1978). If any environmentally related change in heart rate was observed, the anesthesia level was supplemented by sodium pentobarbital.…”
Section: Methodsmentioning
confidence: 78%
“…or i.m. morphine in normal therapeutic doses are 80 ng/mL (38). In one comprehensive review (39), analgesia in cancer patients was associated with steady-state concentrations of morphine in plasma ranging from 6 to 364 ng/mL.…”
Section: Discussionmentioning
confidence: 99%